Factors influencing the awareness and purchase of "green" cosmetics - Leow, Simone Monque Yung Siew (2015)
Much research has been done on the purchase intention and awareness level of environmental-friendly products in general. It has been noted, however. that none of these studies address a specific environmental-friendly product. As such, this study examines the purchase intention and awareness level of female Singaporeans towards green cosmetics. A modification of the Ajzen and Fishbein's Theory of Reasoned Action was used to highlight factors, such as subjective norms and attitude towards behaviour, that can influence behavioural intention. Factor Analysis, Regression Analysis and the Chi-Squared Test of Independence were performed on the data collected. The demographic and sociopsychological characteristics of respondents who responded positively to green cosmetics were found. The results revealed that socially responsible consumers tend to have a higher awareness level and positive purchase intention towards green cosmetics. Awareness level was found to be higher in consumers who were between the age of 16-35 and whose monthly income was $2000 and above. These consumers tend to have received a high level of education and majority of them were executives, managers and professionals. It was also found that generally, women perceived green cosmetics as inexpensive, high quality and image as well as easily available in Singapore. On the whole, the findings on subjective norms and attitude towards behaviour showed that there was no significant relationship between behavioural intention and purchase intention. Consequently, this report offers specific implications for the findings and future research will also be discussed.